2013
DOI: 10.1007/s10549-013-2460-y
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic relevance of Ki-67 in the primary tumor for survival after a diagnosis of distant metastasis

Abstract: Prediction of the prognosis for metastatic breast cancer patients depends on molecular subtypes similar to those found in patients with primary breast cancer. Several studies have shown that estrogen receptor (ER) and progesterone receptor (PR) status determine the course of the disease and the prognosis. As Ki-67 helps to differentiate molecular subtypes in patients with primary breast cancer, the aim of this study was to assess the prognostic relevance of Ki-67 in the primary tumor in relation to its prognos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
12
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 52 publications
3
12
0
Order By: Relevance
“…In former studies, Ki-67 has also been valued as a prognostic factor being associated with breast cancer outcomes [3, 30, 36, 45–49]. Ki-67 previously has been already considered as a biomarker for therapeutic decision [13, 50]. Colozza et al [51] reviewed the role of proliferation markers as prognostic and predictive tools in early breast cancer.…”
Section: Discussionmentioning
confidence: 99%
“…In former studies, Ki-67 has also been valued as a prognostic factor being associated with breast cancer outcomes [3, 30, 36, 45–49]. Ki-67 previously has been already considered as a biomarker for therapeutic decision [13, 50]. Colozza et al [51] reviewed the role of proliferation markers as prognostic and predictive tools in early breast cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Ki67 is the most widely studied proliferation marker in breast cancer; however, the role of Ki67 in breast cancer management remains controversial due to the lack of specificity and reproducibility . For the last decade, PHH3 has attracted attention as a prognostic marker of breast cancer, and a recent study by Gerring et al revealed that PHH3 has a stronger prognostic value than Ki67 in breast cancers.…”
Section: Discussionmentioning
confidence: 99%
“…Ki67 is a DNA‐binding protein expressed in all active phases of the cell cycle except for G0 . Ki67 has been commonly used as a biomarker to predict outcomes of patients with breast cancer; however, its utility has long been under debate because of conflicting reports . Histone H3, one of the core histone proteins, is a major component of chromatin .…”
Section: Introductionmentioning
confidence: 99%
“…One strength is the single-center, uniform assessment of ER, PR, Ki-67, and HER2. Clinical uses of these data have been described in several previous studies (Wiesner et al, 2009;Fasching et al, 2011;Heusinger et al, 2012b;Loehberg et al, 2013). All Ki-67 data, as well as all other immunohistochemical data, were assessed directly at the time of the diagnosis, ensuring direct assessment of molecular subtypes according to the relevant markers.…”
Section: Discussionmentioning
confidence: 99%